Case Report: When dual immune checkpoint blockade strikes back: cadonilimab-induced hypersensitivity in solid tumors — a case series and review - Song, Ping; Jin, Yuqi; Fu, Linglin; Yang, Fengming; Tan, Yinuo (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have revolutionized cancer therapy, but immune-related hypersensitivity reactions remain a clinical concern. Cadonilimab, a novel PD-1/CTLA-4 bispecific antibody, has demonstrated encouraging antitumor efficacy across various solid tumors; however, hypersensitivity or infusion-related reactions may occasionally occur.MethodsWe herein report five cases of cadonilimab-induced allergic or infusion-related reactions in patients with different advanced solid tumors. Clinical manifestations ranged from mild skin rash to severe anaphylaxis with hypotension. All patients were managed promptly with individualized anti-allergic interventions, and some were able to safely continue therapy with modified infusion protocols.ResultsThe series emphasizes the importance of early identification and tailored management of hypersensitivity reactions during cadonilimab treatment. Additionally, a comprehensive literature review was conducted summarizing current clinical trials, case reports, and real-world evidence regarding cadonilimab’s efficacy and safety across multiple cancer types.ConclusionOur findings highlight both the potential risks and manageable nature of cadonilimab-induced hypersensitivity, supporting its continued clinical application with appropriate monitoring and management strategies.